2018
DOI: 10.1039/c8en00194d
|View full text |Cite
|
Sign up to set email alerts
|

Application of graphene-based materials in water purification: from the nanoscale to specific devices

Abstract: The synthesis, multilevel structural features, adsorption performance and environmental applications of graphene nanosheets and 2D/3D graphene-based macrostructure material were summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 272 publications
0
61
0
Order By: Relevance
“…Another type of carbon nanomaterial, graphene, is a planar honeycomb-shaped nanomaterial consisting of six-member rings with a large specific surface area (theoretical value of 2630 m 2 g −1 ) [13]. It is more easily prepared than CNT and shows an extensive application prospect in the removal of organic and inorganic pollutants [14] and dyes [15,16]. Graphene could be modified to adsorb pollutants via π-π, electrostatic interaction and hydrogen bonding.…”
mentioning
confidence: 99%
“…Another type of carbon nanomaterial, graphene, is a planar honeycomb-shaped nanomaterial consisting of six-member rings with a large specific surface area (theoretical value of 2630 m 2 g −1 ) [13]. It is more easily prepared than CNT and shows an extensive application prospect in the removal of organic and inorganic pollutants [14] and dyes [15,16]. Graphene could be modified to adsorb pollutants via π-π, electrostatic interaction and hydrogen bonding.…”
mentioning
confidence: 99%
“…Since then, multiple researchers have shown that laser scribing could be used to design electrodes to sense biomolecules by using infrared and ultra-violet light lasers [93][94][95][96]. While graphene is indeed a useful material in sensing, one of its problems is the tendency of graphene and graphene oxide to bind to a variety of materials in aqueous phase [97]. For this reason, sensor labs typically metallize graphene electrodes with a noble metal that has a specific interaction with mercury ions.…”
Section: Alerting Mercury Exposure In Artisanal Gold Mining Communitiesmentioning
confidence: 99%
“…Recently, new graphene-based three-dimensional (3D) macrostructures with enhanced sorption capability towards hazardous organic molecules and heavy metal(loid)s have been proposed [ 14 , 15 , 16 , 17 , 18 ]. Graphene consists in a single atomic layer of graphite with bond length between carbon–carbon of 0.142 nm and, like graphite, the atoms in graphene are arranged in a hexagonal lattice.…”
Section: Introductionmentioning
confidence: 99%